17β-Estradiol inhibits intervertebral disc degeneration by down-regulating MMP-3 and MMP-13 and up-regulating type II collagen in a rat model. (5th November 2018) - Liu, Sen; Yang, Si-Dong; Huo, Xi-Wei; Yang, Da-Long; Ma, Lei; Ding, Wen-Yuan
Abstract: Objectives: This study was aimed to further explore whether estradiol (E2) had protective effects on intervertebral disc degeneration (IVDD) in a rat model. Material/methods: Forty, three-month-old female Sprague Dawley (SD) rats were randomly divided into four groups: Sham, Ovariectomy (OVX), E2 and ICI182780 (ICI). Sham group only underwent the resection of a bit fat; OVX group underwent bilateral ovariectomy; E2 group was treated with E2 based on OVX; ICI group was treated with E2 and pretreated ICI182780 (inhibitor of the estrogen receptor) based on OVX. Radiography, hematoxylin and eosin (HE) staining, immunohistochemistry (IHC), western blot and quantitative real-time PCR (qRT-PCR) were applied to detect the apoptosis characteristics of intervertebral disc cells. Results: Radiographs showed marked intervertebral disc narrowing and HE staining showed typical apoptosis characteristics of intervertebral disc cells in OVX, which were reversed by E2. Furthermore, the results of IHC, Western blot and qRT-PCR revealed that OVX-induced IVDD was protected by E2 through decreasing the expression of caspase-3 and intracellular matrix metalloproteinases (MMPs), including MMP-3 and MMP-13, while increasing the expression of collagen Type II. All of the detected effects of E2 were abolished after treatment with ICI182780. Conclusion: 17β-E2 inhibits IVDD by down-regulating MMP-3 and MMP-13 and up-regulating collagen Type II in a rat model.